Burns from acetylene gas: more than skin deep. (19th May 2014) - Al-Hassani, Fawaz; Amin, Kavit; Lo, Steven
Abstract : Oxyacetylene welding torches are commonly used in industry, yet serious burns are fortunately rare. When dealing with the sequelae of these burn injuries, one must be aware of the high pressure component of these flame burns, which can penetrate and dissect the subcutaneous tissue. Appropriate initial assessment and preoperative planning are, therefore, essential to exclude and identify problems such as, compartment syndrome, subcutaneous emphysema and acute carpal tunnel syndrome. We present a case in which an innocuous palmar burn revealed a penetrating flame injury into the carpal tunnel.